1989
DOI: 10.1002/jmv.1890270408
|View full text |Cite
|
Sign up to set email alerts
|

Detection of group C rotaviruses in Tokyo

Abstract: Four human group C rotaviruses were detected in Tokyo in 1987 and 1988 during a survey over 7 years. Among the four rotaviruses, two electrophoretic patterns were indicated by polyacrylamide gel electrophoretic (PAGE) analyses. Clinical symptoms, signs, family history, and patients' ages varied. Group C rotaviruses were found also in other parts of Japan in 1988. It was suspected that group C rotaviruses would continue to spread throughout Japan within the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Although several investigators have reported on the E type variation of CHRV field isolates [Penaranda et al, 1989;Ushijima et al, 1989;Schnagl et al, 2004], none have critically classified the E types of these isolates. In group A rotaviruses, E typing of field isolates is a useful tool for obtaining epidemiological information about the origin of the isolates and the diversity among these isolates, because each isolate reveals a unique genome profile [Ahmed et al, 1991;Bass and Greenberg, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Although several investigators have reported on the E type variation of CHRV field isolates [Penaranda et al, 1989;Ushijima et al, 1989;Schnagl et al, 2004], none have critically classified the E types of these isolates. In group A rotaviruses, E typing of field isolates is a useful tool for obtaining epidemiological information about the origin of the isolates and the diversity among these isolates, because each isolate reveals a unique genome profile [Ahmed et al, 1991;Bass and Greenberg, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Although similar Gp B outbreaks have not yet been reported outside China, recent descriptions of the association of Gp C rotaviruses with sporadic cases and a few outbreaks of diarrhea in several countries indicate that the latter group is globally distributed, and perhaps may emerge as an important new pathogen [1,3,[7][8][9]22]. For example, Gp C rotavirus outbreaks have been reported in several different areas of Japan [14,20,28]: in Matsuyama since 1988, Gp C rotavirus has been the most frequently identified virus in stool specimens in ill children 4 to 7 years of age [14]; human Gp C rotavirus infection was also reported in Tokyo in 1987 and 1988 during a 7 year survey [28]; and in Fukui, a large outbreak occurred among schoolchildren and their teachers at seven elementary schools in 1988 [20]. In addition, one fatal case of gastroenteritis associated with Gp C rotavirus has recently been reported in England [8].…”
mentioning
confidence: 98%
“…Since then, they have been recognized in humans and animals, both in industrialized countries including Australia, United States, United Kingdom, Finland, and Japan and in developing countries or regions such as India, China, Malaysia, and Latin America (3,4,5,8,10,18,22,26,29,41). Thus, group C rotavirus strains are globally distributed and are thought to be one of the emerging pathogens in humans.…”
mentioning
confidence: 99%